Implementation of Guidance and Counseling in Islamic Boarding School - Rasyadi, Ahmad Fitra; Albaar, Ragwan; Suwatah, Suwatah (Jurusan Bimbingan dan Konseling Islam, 2023)
The purpose of this research is to find out how the implementation of guidance and counseling at Islamic boarding schools, whether within formal education or outside of it, The study about it was part of a systematic literature review. Studiesprimary in this study were obtained from websites with the provisions of articles using Guidance and Counseling, Islamic Boarding Schools, published on range year 2014-2020, written by Indonesian and English, as well as the title or abstract in accordance with the research objectives. The results from the primary studies used in this research show that the implementation of guidance and counseling at Islamic boarding schools has been carried out in different ways at each school. Implementation and Guidance Counseling at Islamic Boarding Schools, which implement two curricula at once, namely formal education and non-formal, could be used side by side with the Comprehensive Guidance and Counseling program.